House at 1724 The Alameda - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a house with a fountain in front. The architecture is in the Spanishl style The numbers read 1724. Handwritten in pencil on verso of photograph: "On The Alameda."